Analisis Sentimen Pinjaman Online Di Media Sosial Twitter Menggunakan Metode Naive Bayes - Muhammad Imam Ghozali; Wibowo Harry Sugiharto; Ary Fajar Iskandar (STMIK Budi Darma, 2023)
Sentiment analysis is conducted to measure public opinion tendencies towards ongoing or past events. One of the cases analyzed in this study is Online Loans, commonly known as